FINANCIAL RATIO'S IMPACT ON FINANCIAL DISTRESS: PRE- AND DURING THE COVID-19 PANDEMIC - Stefanus Dimas Saputro; Jennyfer Natania (Universitas Pelita Harapan, 2023)
The purpose of this research is to examine the effects of several financial ratios on financial distress prior to and during the COVID-19 pandemic. The research sample consists of 51 basic industrial and chemical businesses that are listed on the Indonesia Stock Exchange between 2018 and 2021. The Springate model is employed to assess the level of financial distress, and logistic regression is used as the analytical method. Liquidity, activity, leverage, profitability ratios and control variables had a significant impact on financial distress both before and during the COVID-19 pandemic. This suggests that these financial ratios, along with other controlled factors, collectively influenced financial distress. The study aims to offer significant perspectives to the audience and function as a guide for prospective investigators and enterprises, namely those operating in the chemical and basic industrial sectors listed on the Indonesia Stock Exchange. It highlights the importance of financial ratios in improving a company's performance and financial condition, which can help minimize financial distress.